The Influence of TikTok on Undergraduate Students’ Academic Performance and Self-Esteem in Azerbaijan - Babazada, Zumrud (ADA University, 2025)
Since TikTok becomes one of the fast-growing social media platforms in Azerbaijan, its possible negative or positive influences on students’ academic lives and emotional states emerge concerns. This study explores the influence of TikTok usage on the undergraduate students’ academic performances and self-esteem in Azerbaijan by using qualitative research methods. The aim of the study is to investigate how TikTok’s content, algorithm, user patterns, and their time spent on TikTok affect undergraduate students’ motivation, concentration, behavior, time management, self-esteem and academic outcomes. The data was collected from six undergraduate students from three different universities in Azerbaijan and one social media expert through indepth semi-structured interviews. This study uses Self-Determination Theory (SDT) as a theoretical background for data analysis, explaining the study findings through the three basic needs: relatedness, competence, and autonomy. The results of the study demonstrated that while some participants found educational and motivational content beneficial in their academic lives, most reported negative effects of TikTok such as procrastination, reduced attention span, and lowered self-esteem. The findings also shed light on how social comparisons and feedback (e.g. likes, comments, reposts) on TikTok influence students’ self-esteem levels and emotions
Keywords: Social media and education -- Azerbaijan; Social media -- Psychological aspects; TikTok’s influence; Time management -- Study and teaching (Higher) -- Azerbaijan; Academic achievement -- Azerbaijan; Education